Charity Tithe in Deuteronomy as a Mechanism for Funding Poverty Alleviation Programmes in the Anglican Diocese of Ogbomoso, Nigeria (2014)
Charity Tithe (CT) in Deuteronomy was used to provide palliatives for the poor in Ancient Israel. Contrariwise, while groups likened to these are found in Nigerian churches, especially the Anglican Church, CT is not adopted, resulting largely in loss of members to other denominations practising a similar system. Existing studies on tithing and church poverty alleviation have addressed the obligatory nature of tithing, but little attention has been paid to the welfare values of CT as practised in Ancient Israel and as related to the Anglican Church. This study, therefore, examined the practice of CT and its effectiveness in Deuteronomy with a view to justifying the need for its existence in the Anglican Church and relevance in addressing poverty and membership situations in the Anglican Diocese of Ogbomoso (ADO). The study adopted the theoretic concept of “The Community of Goods in the Early Church”. The ADO was purposively selected because poverty alleviation is one of its main programmes. Four hundred copies of a questionnaire were administered to 40 clergymen, and 60 lay members each from the five archdeaconries and the Cathedral. In-depth interviews were conducted with 60 respondents involved in the Diocesan poverty alleviation programmes: 25 Clergymen and 35 lay members. Six focus-group discussions (FGDs) were held with ten members in each Archdeaconry and the Cathedral. Church membership/tithe records were consulted. Biblical texts (Deuteronomy 14:28-29; 26:12-15) were exegetically analysed, and quantitative data were subjected to percentages. Charity tithe in Deuteronomy, which was paid by every adult Israelite once in three years on agricultural products and stored in the clan gate, was used to tackle hunger (Deut. 14:28-29; 26:12-15). In the ADO where many of the population lived below poverty line, CT was non- existent, which caused a level of membership loss, but close to it was an offertory offering misconstrued by 72.4% interview respondents (clergymen: 37.0% and laity: 35.4%) as CT collected weekly for the poor. This generated ₦3.7m between 2005 and 2013 and catered only for 4.0% of the poor; 7.0% (27 people annually) of these left for other churches. A projective analysis from the questionnaire indicated that a faithful execution of CT would yield greater effects, generating ₦14.6m every three years from: farmers (1470:₦2.5m), civil-servants (315:₦6.5m), traders (525:₦2.8m), employees of private sectors/retirees/clergy (210:₦1.2m), artisans (385:₦1.5m), and students (595:₦120,000). These resources would have the following distribution: clergy (45:17%:₦2.4m), widows (113:18%:₦2.6m), orphans (121:20%:₦2.9m), strangers (322:23%:₦3.3m) and the unemployed (313:22%:₦3.2m). While 92.0% interview respondents supported the adoption of CT in empowering priests’ wives, orphans, youths and women, many of FGD participants opined that rural dwellers should be given priority in the distribution. Moreover, majority of the participants agreed that it would reduce the exodus of poor members to other churches. Charity tithe was non- existent in the Anglican Diocese of Ogbomoso, which, among other factors, led to loss of members. Given the success of the practice in Deuteronomy and its potential effectiveness in the Diocese, its adoption and faithful implementation by the Anglican Church would alleviate poverty and enhance evangelism